The Generating Function of a Bi-Periodic Leonardo Sequence - Carlos M. da Fonseca
In “A note on bi-periodic Leonardo sequence”, thegenerating function for a certain biperiodic Leonardo sequenceis claimed. In this note, based on the literature, we establish thecorrect identity. Possible periodic extensions for the Leonardosequence are discussed, opening new avenues for results in thearea
Keywords: Mathematics